(untitled) (Computer systems and information technologies, 2022)
This article considers the expansion of the capabilities of digital devices of three-pulse suppression of the request of aircraft responders with side petals in terms of increasing the accuracy of measuring the azimuth of flight of aircraft. In existing devices, the response of aircraft responders is carried out at the time of the boundary crossing by the aircraft of the frequency pattern of the antenna. The directional pattern of the radar systems of the main petal has an angle of 2o-4o in the horizontal plane depending on the type of radar system and the request period of terrestrial radar stations is 500 Hz, and the antenna rotation speed is 10 rpm and the distance between pulses P1 and P3 is 14 μs. The time the aircraft is within the directional pattern of the main petal will be requested 17 times and the same number of responses, which in turn leads to ambiguity in fixing the definition of the aircraft in azimuth, especially over long distances. The response of the aircraft respondent to the request will be answered when approaching the middle of the directional pattern of the antenna of the main lobe, where the highest power of the emitted signal, which will significantly reduce the error of determining the aircraft by azimuth